PENINGKATAN HASIL BELAJAR DARING PESERTA DIDIK SELAMA PANDEMI COVID-19 MELALUI PEMANFAATAN FITUR APLIKASI ZOOM DI SD NEGERI 77 PALEMBANG - Indra Gunawan (Universitas Sriwijaya, 2020)
This Classroom Action Study was aimed at describing the online learning outcomes improvement and learning process of Grade VI students in Public Elementary School 77 Palembang through the using of Zoom Aplication. The research was conducted through two cycles of action. The diagram shows that the exhaustiveness increased from cycle I at 47% to 88% after cycle II. The learning outcomes also improved from cycle I to II at 63.8 and 82.9 respectively. This study concluded that through the using of Zoom Application, there will be improvement at online learning outcomes in thematic learning.Keywords: Learning Outcomes, Online Learning, Zoom Application